English Grammatical Usage : a study guide - Simon-Vandenbergen, Anne-Marie, 1949-; Taverniers, Miriam, 1974- (Leuven : Acco, 2016)
As a study guide to enhance your insight into English grammatical usage, this book distinguishes itself from the merely practical, pedagogical school grammar on the one hand and the specialized linguistic grammar on the other hand. Targeted at advanced learners of English (Common European Framework level B1-B2) with an interest in the linguistic study of language, this book will be of particular interest to first- (and second-) year university students and students of other institutes of higher education who wish to acquire an insight into the grammatical usage of English. More generally, it hopes to reach anyone with a similar interest. It can be used as a course text in advanced EFL classes at university or college level, as a reference for any course addressing aspects of English grammatical usage, or as a book for self-study. Both authors are experienced EFL teachers at university level, and experts in English grammar.
Keywords: grammar